2018
DOI: 10.1016/j.juro.2018.02.827
|View full text |Cite
|
Sign up to set email alerts
|

V03-02 First Clinical Study on Superpulse Thulium Fiber Laser for Lithotripsy

Abstract: INTRODUCTION AND OBJECTIVES: We investigated the prognostic significance of the various manifestations of extrarenal extension which comprise pathologic stage T3a renal cell carcinoma (RCC) among patients treated with extirpative therapy for nonmetastatic disease.METHODS: A retrospective review of 595 patients who underwent nephrectomy for pathologically-confirmed T3aN0/NxM0 clear cell RCC between 1970 and 2011 was performed. All pathologic slides were re-reviewed by a single urologic pathologist. Associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 0 publications
1
29
0
2
Order By: Relevance
“…Comparing laser setting options, TFL offers frequencies of 5-2200 Hz, pulse energies of 0.025-6 J, and pulse durations of 200-12,000 microsec [76,[80][81][82][83], whereas Ho:YAG offers 5-100 Hz, 0.2-6 J, and 50-1300 microsec [81,84]. These qualities of the TFL laser give this technology the potential to produce 3-4 times more dust compared to high-power Ho-YAG lasers [78,85,86]. Furthermore, due to the novel laser beam generation by laser diodes in TFL, smaller fibres (50 µm) can be utilized, which may result in higher energy intensity at the tip of the fibre, better scope deflection, and better irrigation, all of which can potentially increase stone ablation volume at comparable settings [74,80,81].…”
Section: Comparison Of Different Laser Technologies For Intracorporeal Lithotripsymentioning
confidence: 99%
“…Comparing laser setting options, TFL offers frequencies of 5-2200 Hz, pulse energies of 0.025-6 J, and pulse durations of 200-12,000 microsec [76,[80][81][82][83], whereas Ho:YAG offers 5-100 Hz, 0.2-6 J, and 50-1300 microsec [81,84]. These qualities of the TFL laser give this technology the potential to produce 3-4 times more dust compared to high-power Ho-YAG lasers [78,85,86]. Furthermore, due to the novel laser beam generation by laser diodes in TFL, smaller fibres (50 µm) can be utilized, which may result in higher energy intensity at the tip of the fibre, better scope deflection, and better irrigation, all of which can potentially increase stone ablation volume at comparable settings [74,80,81].…”
Section: Comparison Of Different Laser Technologies For Intracorporeal Lithotripsymentioning
confidence: 99%
“…Potential advantages of TFL technology have recently been reviewed in the literature . While the majority of previous reports have been based on preliminary laboratory studies , the TFL has also shown promise in early clinical studies as well . Electronic modulation of the diode‐pumped TFL enables it to be operated with a wide range of laser parameters, including pulse energies from 5 mJ up to 6 J, pulse durations of 100 μs to 100's of ms, and pulse rates of 1–2,000 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…The initial clinical experiences have demonstrated that the different laser settings used in the operating room are safe for patients. Many combinations of laser settings have been tested for ureteral, renal, and bladder stone lithotripsies presented in various conference abstracts [ 9 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] and in full-text clinical experiences [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ] ( Table 2 ). However, the ideal one has not yet been established.…”
Section: Resultsmentioning
confidence: 99%
“…The TFL showed its appealing characteristics in several preclinical studies, possessing the widest and most flexible range of parameters among the actual laser lithotripters [ 7 , 8 ]. Later on, the first clinical trial was developed in Russia in 2018, making it the only country with clinical approval given by the Ministry of Health of the Russian Federation [ 9 ]. It was only in June 2020 that this technology was approved worldwide with incredible results [ 6 ].…”
Section: Introductionmentioning
confidence: 99%